A Novel FtsZ-Like Protein Is Involved in Replication of the Anthrax Toxin-Encoding pXO1 Plasmid in Bacillus anthracis - Tinsley, Eowyn (American Society for Microbiology, 2006)
Plasmid pXO1 encodes the tripartite anthrax toxin, which is the major virulence factor of Bacillus anthracis. In spite of the important role of pXO1 in anthrax pathogenesis, very little is known about its replication and maintenance in B. anthracis. We cloned a 5-kb region of the pXO1 plasmid into an Escherichia coli vector and showed that this plasmid can replicate when introduced into B. anthracis. Mutational analysis showed that open reading frame 45 (repX) of pXO1 was required for the replication of the miniplasmid in B. anthracis. Interestingly, repX showed limited homology to bacterial FtsZ proteins that are involved in cell division. A mutation in the predicted GTP binding domain of RepX abolished its replication activity. Genes almost identical to repX are contained on several megaplasmids in members of the Bacillus cereus group, including a B. cereus strain that causes an anthrax-like disease. Our results identify a novel group of FtsZ-related initiator proteins that are required for the replication of virulence plasmids in B. anthracis and possibly in related organisms. Such replication proteins may provide novel drug targets for the elimination of plasmids encoding the anthrax toxin and other virulence factors.